2014
DOI: 10.1189/jlb.3ri0413-217rr
|View full text |Cite
|
Sign up to set email alerts
|

Tumor formation and antitumor immunity; the overlooked significance of histamine

Abstract: HA is a biogenic amine, widely distributed throughout the body. Given the observations that HA, the decarboxylated amino acid histidine, can be induced and made available in an unstored, diffusible form in tissues undergoing rapid growth (such as tumors and regenerating tissues), it could have a role in antitumor response beyond the well-studied inflammatory and allergic responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Histamine is a biogenic amine which is widely distributed and has many functions 4 5 6 7 . Several studies have found that the levels of histamine in the serum and myocardium increased significantly in acute myocardial infarction (AMI) 8 9 10 11 12 .…”
mentioning
confidence: 99%
“…Histamine is a biogenic amine which is widely distributed and has many functions 4 5 6 7 . Several studies have found that the levels of histamine in the serum and myocardium increased significantly in acute myocardial infarction (AMI) 8 9 10 11 12 .…”
mentioning
confidence: 99%
“…Elevated quantities of histamine have been detected in some malignancies such as breast, prostate, ovarian, cervical-and lung cancer (Kubecova et al, 2011). Various types of malignant cells also express the H2 receptor, and histamine may directly induce the expansion of certain tumor cells and/or exerts pro-tumor activities through H2 receptor-mediated immune suppression (Falus and Gilicze, 2014;Faustino-Rocha et al, 2017;Jafarzadeh et al, 2019). The overexpression of COX-2 and PGE2 was also reported in cancerous cells, which are related to tumor progression and resistance to current therapeutic elements (Pang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Histamine is a biogenic amine involved in a variety of physiological and pathophysiological functions in the context of allergic responses, gastric acid secretion, immune modulation, and carcinogenesis4567. Although increases in histamine levels during the early stage of MI have been documented8910, the origin and effects of histamine with respect to the development of heart failure post-MI, as well as the mechanisms underlying these effects, are still controversial.…”
mentioning
confidence: 99%